2019
DOI: 10.1142/s1793292019501583
|View full text |Cite
|
Sign up to set email alerts
|

Development of Gold Nanorods-Insulin Amyloid Fibril Assemblies: A Hybrid Nanoscaffold with Enhanced Conductivity

Abstract: Gold nanoparticles are metallic nanostructures with wide range of applications in biomedicine and biosensing. Among diverse morphologies of gold nanostructures, gold nanorods have attracted much more attention for their outstanding structure, optical property and function. The unique characteristic of these nanostructures encourages their integration with biomolecules of interest for versatile biomedical proposes. In this effort, amyloid fibrils with well-known mechanical strength and chemical stability have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Reynolds et al revealed that lysozyme amyloid brils can enhance the attachment and spreading of cells [39]. Akhtari et al developed Gold nanorods-Insulin amyloid bril assemblies with improved conductivity for future sensing and tissue engineering platforms [40].…”
Section: Antimicrobial Susceptibility Testingmentioning
confidence: 99%
“…Reynolds et al revealed that lysozyme amyloid brils can enhance the attachment and spreading of cells [39]. Akhtari et al developed Gold nanorods-Insulin amyloid bril assemblies with improved conductivity for future sensing and tissue engineering platforms [40].…”
Section: Antimicrobial Susceptibility Testingmentioning
confidence: 99%